Mutagenic exploration of the active site of lactate dehydrogenase from Plasmodium falciparum - Turgut-Balik, D; Shoemark, DK; Sessions, RB; Moreton, KM; Holbrook, JJ (Kluwer Academic Publ, 2001)
Several site-directed mutations of residues around the active site of the lactate dehydrogenase from Plasmodium falciparum are described. These include changes to three highly, but not completely, conserved residues in the pocket of the active site and also three changes (including deletions) to the active site loop. Changes to residues in the active-site pocket resulted in little or no over-production of protein and no enzymic activity. Likewise, a five residue deletion from the active site loop gave no over-produced protein, while a two residue deletion and changes of residue type in this loop were tolerated. The results are discussed in the light of this protein being a suitable target for novel anti-malarials.
Keywords: anti-malarials; drug resistance; enzyme; malaria; substrate-specificity loop